Structural features determining the vitamin K epoxide reduction activity in the VKOR family of membrane oxidoreductases. (10th February 2022) - Shen, Guomin; Li, Chaokun; Cao, Qing; Megta, Abhin Kumar; Li, Shuang; Gao, Meng; Liu, Hongli; Shen, Yan; Chen, Yixiang; Yu, Haichuan; Li, Sanqiang; Li, Weikai
Abstract : Vitamin K epoxide reductases (VKORs) are a large family of integral membrane enzymes found from bacteria to humans. Human VKOR, specific target of warfarin, has both the epoxide and quinone reductase activity to maintain the vitamin K cycle. Bacterial VKOR homologs, however, are insensitive to warfarin inhibition and are quinone reductases incapable of epoxide reduction. What affords the epoxide reductase activity in human VKOR remains unknown. Here, we show that a representative bacterial VKOR homolog can be converted to an epoxide reductase that is also inhibitable by warfarin. To generate this new activity, we first substituted several regions surrounding the active site of bacterial VKOR by those from human VKOR based on comparison of their crystal structures. Subsequent systematic substitutions narrowed down to merely eight residues, with the addition of a membrane anchor domain, that are responsible for the epoxide reductase activity. Substitutions corresponding to N80 and Y139 in human VKOR provide strong hydrogen bonding interactions to facilitate the epoxide reduction. The rest of six substitutions increase the size and change the shape of the substrate‐binding pocket, and the membrane anchor domain stabilizes this pocket while allowing certain flexibility for optimal binding of the epoxide substrate. Overall, our study reveals the structural features of the epoxide reductase activity carried out by a subset of VKOR family in the membrane environment. Abstract : Vitamin K epoxide reductases (VKORs) are a family of integral membrane oxidoreductases found from bacteria to humans. Human VKOR reduces vitamin K epoxide to support blood coagulation, whereas bacterial homologs can only reduce quinones. Here, we convert a representative bacterial VKOR to epoxide reductase by merely changing eight residues (orange) and adding a membrane anchor domain found in human protein. These changes in local structure, not overall fold, determine the epoxide reductase activity.